Correlation between Endoscopy Finding with Clinical Manifestations of Recurrent Abdominal Pain and Helicobacter pylori Infection - Ermaya, Yudith Setiati; Prasetyo, Dwi (Perdatin Pusat, 2015)
Recurrent Abdominal Pain (RAP) is abdominal pain that occurs three times or more within 3 months that can interfere with daily activities for children. Prevalence of RAP 10%–30%, with functional or organic causes. Organic causes include infection with Helicobacter pylori (H. pylori). Globally >50% of the world’s population is infected with H. pylori, especially in developing countries, as the gold standard histological examination using an endoscope with anesthesia. This research to found the correlation between the endoscopic finding with clinical manifestations RAP and H. pylori infection. A cross-sectional study was conducted on 20 patients with complaints RAP children who come to the Hospital Dr. Hasan Sadikin, the period April–November 2015. Analysis using Pearson Chi-square, Spearman rho, Fisher’s exact and Mann-Whitney test. Subject as 20 children, consisting of 10 boys and 10 girls, median age 12 years, most clinical manifestations are RAP 60% and 80% erosion endoscopic finding. There were no significant correlation between the endoscopic finding with clinical manifestations, but have tendency endoscopic finding worse with severe clinical manifestations. Infection of H. pylori found positive in 90% subjects, boys 55%, there is no significant correlation between the endoscopic finding with H. pylori infection (p=0.133). Conclusions not found a significant correlation between endoscopy finding with clinical manifestations and H. pylori infection.